THE ROLE OF YOUTH PARTICIPATION AND LEADERSHIP IN ENHANCING THE SOCIAL CONTRIBUTION OF YOUTH PIONEERS IN INDONESIA - Albert; Gonawi, Zivanka; Utomo, Clinton; Hasan, Delfine Pangloli; Khu, Derrick Cristian (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to analyze the influence of youth participation and youth leadership on the social contributions of Pemuda Pelopor (Pioneering Youth) in Indonesia. The research employed a quantitative approach with a causal associative design. The study population consisted of Pemuda Pelopor registered in the 2023 program of the Ministry of Youth and Sports (Kemenpora), with a sample of 120 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with SPSS version 26, including validity and reliability tests, multiple linear regression, as well as F-test and t-test analyses. The results revealed that: (1) youth participation has a positive and significant effect on social contribution; (2) youth leadership has a positive and significant effect on social contribution; and (3) youth participation and youth leadership simultaneously have a significant effect on the social contribution of Pemuda Pelopor. These findings reinforce Social Participation Theory and Transformational Leadership Theory, emphasizing that active involvement and visionary leadership play crucial roles in fostering awareness and collective social action among youth. The study’s outcomes are expected to serve as a reference for developing youth empowerment policies and programs that are more participatory, collaborative, and sustainable in Indonesia